Opinion Leader Strategies in Preventing HIV/AIDS Transmission among Commercial Sex Workers in Bongsuwung Prostitution Area in Yogyakarta - Zahrotus Sa'idah; Novita Ika Purnama Sari; Fiqo Syafril Syaiful Anwar; Muhammad Adjie Prayitno (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
This research was conducted in response to the increasing cases of HIV/AIDS in Yogyakarta, particularly those caused by heterosexual groups, with a focus on the Bong Suwung prostitution area. The objective of this research is to understand the strategies employed by opinion leaders in suppressing the transmission of HIV/AIDS among commercial sex workers in that area. This research uses a qualitative method involving observation, interviews, and documentation, revealing two types of strategies - general and specific - involving steps such as routine health check-ups, affordable condom distribution, regular meetings, socialization, and the establishment of specialized associations. There are challenges in conducting this research, including low education, difficult economic conditions, age factors, and social stigma. Intensive approach strategies that are relevant to the theory of social penetration proved successful in building close relationships with sex workers, enabling them to receive more effective information and care. This research underscores the importance of collaboration with various stakeholders in HIV/AIDS prevention efforts, addressing social stigma, and establishing deeper relationships with HIV/AIDS patients. These actions are essential to tackle the complexity of this issue and minimize the spread of HIV/AIDS in prostitution areas like Bong Suwung.